Forming of critical thinking of future primary school teachers as a process - Pochynkova М. (Problems of Engineer-Pedagogical Education, 2021)
Actuality of the research is predefined by the requirements of time, namely by informatization of all social scenes, that need for humen special abilities and skills of work with information. In opinion of the researcher one of such is critical thinking which development must be a purposeful process and provides success with professional activity. Scientific researches of these problematics are devoted mainly to thinking development of school students, however modern higher education in Ukraine needs also introduction of technology of critical thinking, in particular in the process of professional preparation of future primary school teachers. The aim of the article is to expose content and structure of basic pedagogical concepts of the research: development, forming, pedagogical process, pedagogical activity. The tasks involve analysis of scientific pedagogical literature on the issue of the research; differentiation of concepts "forming" and "development", "pedagogical process" and "pedagogical activity"; determination of usage expediency of one or another definition in development of problem of critical thinking forming in the process of professional preparation of future primary school teachers. According to the results of scientific literature analysis the author defined that forming of critical thinking in the process of professional preparation of future primary school teachers as a process is based on main pedagogical concepts: forming and development, pedagogical process and pedagogical activity. It is necessary to separate each definition in certain pairs in pedagogical researches. Development is a specific process of change, the result of which is appearance of qualitatively new ongoing process of ascent from the lowest to the highest, from simple to difficult. In the light of our research it is more appropriate to talk about forming as a process outlined within the limits of time, leaning on technology of development of critical thinking of future primary school teachers. Thus forming is a process and as a research is pedagogical process, so we expose its features as a pedagogical process. The pedagogical process is examined as an activity and system, and the concept "pedagogical activity" is examined as means of realization of pedagogical process.